The Effectiveness of Guided Inquiry Learning Model Using TPS Approach of Science Process Skills and Conceptual Understanding - Suantara, I Kadek Tony; Hartono; Susilaningsih, Endang (International Journal of Elementary Education, 2022)
Science process skills and conceptual understanding of students are still relatively low. Students need a learning model that can support the improvement of student skills. The combination of Guided Inquiry and Think Pair Share can improve students' conceptual understanding and science process skills through every step taken. This study aims to analyze the improvement of science process skills and students' conceptual understanding through Guided Inquiry model with think pair share approach and Guided Inquiry model. This research used quasi-experimental research with Pretest-Posttest Nonequivalent Control Group Design. Determination of the sample used random sampling technique. The sample of this research was fifth graders totaling 53 students. The instrument used was a test of conceptual understanding and science process skills on the theme of heat and its displacement. The data was analyzed using n-gain test and t-test. The results showed that the average of the experimental class was higher than the control class. The results of the discrimination test results on the average of conceptual understanding and science process skills of students obtained that there are differences in science process skills and understanding of students' concepts in guided inquiry class and guide inquiry class with think pair share approach. The effectiveness of this learning model is indicated by the achievement of 3 indicators, that is completeness which exceeds 75%, the average value of process skills and conceptual understanding that exceeds the control class, and the score that increased significantly.